Gender Sensitive Journalism in Harian Kompas as a Media Advocacy Against Women’s Sexual Violence - Islaq Hastita Hamzah; Gati Dwi Yuliana (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2023)
Cases of sexual violence against women are steadily increasing every year, as well as the news of these cases. Despite that, often the media exploits victims and their stories. The news is framed through a patriarchal lens that gives the impression that the victim was the main cause of the events. As a provider of information, the media plays a central role in constructing public opinions. Therefore, the media has a responsibility to support the victims to get their rights. Reporting with gender sensitive journalism is a media reference in advocating for victims/survivors of sexual violence. This study aimed to determine the application of gender sensitive journalism in Harian Kompas as a media advocacy against sexual violence. This study is based on the concept of Gendered Perspective Journalism, Gender Sensitive Journalism, Press Language in Reporting Sexual Violence, and Advocacy Journalism. This research applied qualitative research methods. The results of this study indicated that Harian Kompas covers cases of sexual violence based on the perspective of victims to protect victims and help the survivors to get justice. Furthermore, as a form of advocacy journalism, Harian Kompas also provides a large space for victims to speak out in the Harian Kompas.